Seismic Performance of Instant Steel Frame House for Post Earthquake Reconstruction - Sutrisno, Widarto (Springer, 2022)
Earthquakes in Indonesia revealed that the majority of the destroyed buildings were community dwellings. For instance, the 2006 Yogyakarta earthquake itself caused 390,077 houses collapsed. The recent earthquakes in 2018 that happened in Lombok and Palu again caused 83,392, and 68,451 houses collapsed, respectively. Those collapsed houses were dominated by brick masonry wall type houses, which caused thousands of casualties in each major earthquake. This is due to the fact that the dwellings were not built properly, and this type of system is considered brittle. The casualties were caused mainly by the falling debris of the brick masonry walls. Recently new types of houses are introduced for the reconstruction after the earthquakes to satisfy the slogan Built Back Better. One of the newly introduced types of houses is called Instant Steel Frame House with the Indonesian acronym RISBA that can be built only within several days. The main steel frames of RISBA are made of double canal CNP 95 × 33 × 10 × 1.8 profile. This paper discusses the seismic performance of RISBA by using pushover analysis with SAP 2000 software. To take into account the material non-linearity, flexural plastic hinges were inserted in the frames. Pushover analysis results show that RISBA will respond almost elastically even in the very high seismic region like Palu City in Indonesia. In 2018 experience a big earthquake because especially the RISBA is very light. It is noted that adequate anchorages must be provided in the tie beams to prevent the locking mechanism. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.